The Influence of Transformational Leadership on Employee Motivation - Yusup, Aldian; Maulani, Isma Elan (Green Publisher Indonesia, 2023)
Work motivation is an important factor in achieving organizational goals. One of the factors that can affect work motivation is leadership. Transformational leadership is a leadership model that can influence employee motivation. This study aims to examine the effect of transformational leadership on employee motivation in manufacturing companies. The research method used was a survey with a purposive sampling technique, which took a sample of 150 employees in three different manufacturing companies in the Jakarta area. Data were obtained by distributing questionnaires to respondents and analyzed using multiple linear regression. The results of the study show that transformational leadership has a positive and significant effect on employee motivation. Factors that affect work motivation, such as vision, direction, and employee empowerment, all have a positive influence on employee motivation. The practical implication of the results of this research is that companies must pay attention to and improve transformational leadership within the organization. This can be done by providing leadership training and career development for organizational leaders. Transformational leadership can be an effective strategy in increasing employee motivation, so as to improve overall organizational performance.